2014
DOI: 10.1002/ptr.5236
|View full text |Cite
|
Sign up to set email alerts
|

Extracts from Calendula officinalis Offer in Vitro Protection Against H2O2 Induced Oxidative Stress Cell Killing of Human Skin Cells

Abstract: The in vitro safety and antioxidant potential of Calendula officinalis flower head extracts was investigated. The effect of different concentrations (0.125, 0.5, 1.0, 2.0 and 5.0% (v/v)) of Calendula extracts on human skin cells HaCaT in vitro was explored. Doses of 1.0% (v/v) (0.88 mg dry weight/mL) or less showed no toxicity. Cells were also exposed to the Calendula extracts for either 4, 24 or 48 h before being exposed to an oxidative insult (hydrogen peroxide H2 O2 ) for 1 h. Using the MTT cytotoxicity ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…Cell viability was then tested via MTT assay. The MTT assay showed that cell viability of Vero cells was significantly decreased after treatment officinalis flower extracts contain bioactive and free radical scavenging compounds that significantly protect against oxidative stress in a human skin cell culture model [55].…”
Section: Protective Effect Against Oxidative Stressmentioning
confidence: 99%
“…Cell viability was then tested via MTT assay. The MTT assay showed that cell viability of Vero cells was significantly decreased after treatment officinalis flower extracts contain bioactive and free radical scavenging compounds that significantly protect against oxidative stress in a human skin cell culture model [55].…”
Section: Protective Effect Against Oxidative Stressmentioning
confidence: 99%
“…Therefore, HaCaT cells treated with Calendula extract C to produce bioactivity antioxidant compounds did protect against toxicity of personal care products (beauty products and head lice treatments) that caused oxidative stress cell killing. The protection offered by Calendula extract C was time-dependent as explored early [4,5]. It was noted that there was significantly higher protection after pre-treatment with calendula extract with compounds that displayed higher toxicity when induced by the treatment of compounds alone.…”
Section: Discussionmentioning
confidence: 99%
“…The toxicity results of personal care products on HaCaT cells were measured by MTT assay which is a relative survival assay. Calendula officinalis showed protection activity against hydrogen peroxide (H 2 O 2 ) induced oxidative stress cell killing and chromosomal damage [4,5]. Therefore, HaCaT cells treated with Calendula extract C to produce bioactivity antioxidant compounds did protect against toxicity of personal care products (beauty products and head lice treatments) that caused oxidative stress cell killing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations